Pengaruh Kebijakan Dividen, Struktur Modal, Ukuran Perusahaan dan Profitabilitas Terhadap Nilai Perusahaan - Sidiki, Julio Indra Pratama; D P Aritonang, Reikman (Universitas Muhammadiyah Jakarta, 2025)
Object: This study aims to analyze the effect of dividend policy, capital structure, firm size, and profitability on firm value in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022. Design/Methodology/Approach: Quantitative approach was employed using secondary data obtained from the financial statements available on the official website of the Indonesia Stock Exchange. The study sample comprises 46 publicly listed companies in the consumer goods sector, resulting in a total of 230 firm-year observations. Data analysis was conducted using panel data regression with the assistance of EViews 13 software. Findings: The results indicate that dividend policy and firm size have a positive and significant effect on firm value. In contrast, capital structure and profitability do not have a significant impact on firm value. Theoretical Contribution: This study contributes to the literature by reinforcing signaling theory and agency theory in the context of dividend policy and capital structure. The findings suggest that dividends serve as positive signals to investors, while firm size reflects a company’s competitive strength in the market. Practical/Policy Implications: The results are valuable for corporate management in formulating dividend policies and expansion strategies and assist investors in evaluating firms based on their size and dividend decisions. Limitations: The study is limited to manufacturing firms in the consumer goods sector listed on the IDX and relies solely on secondary data from financial statements. Additionally, Price to Book Value (PBV) data for the year 2017 was excluded due to time and resource constraints. Keywords: Dividend Policy, Capital Structure, Firm Size, Profitability, Firm Value